Contribution of polish inventors to the development of science and technology at the turn of the 19th and 20th centuries - Janusz RYBIŃSKI (Nowoczesne Systemy Zarządzania, 2018)
The article presents the problems concerning the contribution of Polish inventors to the development of science and technology at the turn of the 19th and 20th centuries. Inventors of 100 years ago, who are often forgotten, as well as their inventions, which despite the passage of time accompany us to this day. Such a particular period was the time of the First World War and, as a result, obtaining its own statehood. It is closely related to the establishment of the Patent Office of the Republic of Poland and for the first time in our history the basis for the legal protection of inventions have been developed. On the basis of the legal system adopted at that time and constantly amended, national law, continuously from 100 the Polish Patent Office grants exclusive rights for inventions and utility models submitted for protection in Poland.